Insights from older adults’ lived experience of physical activity and exercise during the COVID-19 lockdown in England - Szekeres, Zsofia; Agustín-Sierra, Noelia; Zaidell, Lisa; Mileva, Katya N.; De Oliveira, Rita F. (Frontiers in Sports and Active Living, 2024)
This study investigated older adults’ emotional and social experiences of physical activity and exercise during the first Covid-19 lockdown in England. Participants were 24 older adults (M=74 years, SD=5.0) either physically active or inactive before lockdown. Semi-structured interviews were conducted at the start of the pandemic in England, and when restrictions were lifted eight weeks later. Template analysis revealed three main themes: a Sense of Purpose for Being Physically Active, Routes for Engagement, and Inactive by Force? with different sub-themes for active and inactive participants The lockdown restrictions emphasised the need to keep physically active in both active and inactive participants, but they perceived barriers differently. Both active and inactive participants found a renewed sense of purpose in walking outdoors for exercise when restrictions eased, enhancing their physical and mental well-being. To reduce barriers and emphasise that exercise is for all ages and all levels of mobility, multi-modal recommendations are presented for educating, promoting, supporting, and enabling older adults to engage in physical activity and exercise.